Evaluasi Perubahan Penggunaan Lahan di Kawasan Rawan Bencana Tsunami Sanur - Hersalita, Anak Agung Indira Yufanda; Rajendra, I G. N. Anom; Agusintadewi, Ni Ketut (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment); Vol 11 No 2 (2024): October 2024DO - 10.24843/JRS.2024.v11.i02.p07, 2024)
The study documented in this article evaluates land use changes in an area prone to tsunami disasters. Sanur is chosen as a medium of study due to its intensive land use changes and geographical position close to the Indo-Australian and Eurasian Plate's collision lines, making it a high tsunami hazard area. While Sanur has had a Tsunami Evacuation Map issued by GITEWS in 2010, this study attempts to review its relevance, considering Sanur has always been targeted by various land use changes. This study uses a qualitative approach with a case study. Data collection methods include remote sensing, semi-structured interviews, and review documents. This research shows that land use classifications are for water bodies, vegetation, rice fields, built-up areas, and coastal plains. An increase in the number of tourism accommodations, land conversion, reclamation, and changes in the coastline causes changes in land utilization. These spatial deviations can potentially cause positive implications, especially in increasing land roughness, increasing the number of Temporary Evacuation Sites (TES), and changing the evacuation mode. However, evacuation zones based on the worst tsunami scenario still need to be planned to minimize the number of victims and damages to the existing infrastructures. Keywords: land use; high danger zone; evacuation zone; tsunami, coastal tourism area   Abstrak Studi yang didokumentasikan di dalam artikel ini mengevaluasi perubahan tata guna lahan di kawasan yang rentan bahaya tsunami. Sanur dipilih sebagai media studi karena perubahan tata guna lahan yang intensif dan posisi geografis yang berdekatan dengan garis tumbukan antara lempeng Indo-Australia dengan Lempeng Eurasia, yang membuatnya sebagai kawasan rentan tsunami. Walau Sanur telah memiliki Peta Evakuasi Tsunami yang dikeluarkan oleh GITEWS pada tahun 2010, studi ini mencoba mengevaluasi relevansi dari peta ini, mengingat Sanur telah secara kontinyu menjadi target perubahan tata guna lahan. Penelitian ini menggunakan pendekatan kualitatif dengan studi kasus. Metode pengumpulan data yang digunakan melingkupi penginderaan jauh, wawancara semi-terstruktur, dan review dokumen. Hasil penelitian menunjukkan klasifikasi penggunaan lahan adalah untuk badan air, vegetasi, sawah, lahan terbangun, dan dataran pantai. Perubahan penggunaan lahan disebabkan oleh peningkatan jumlah akomodasi pariwisata, alih fungsi lahan, reklamasi, dan perubahan garis pantai. Simpangan spasial ini berpotensi menimbulkan implikasi positif, khususnya di dalam meningkatkan kekasaran daratan, menambah jumlah Tempat Evakuasi Sementara (TES), dan mengubah modus evakuasi. Walau demikian, zona evakuasi berdasarkan skenario tsunami terburuk perlu direncanakan untuk meminimalisir jumlah korban dan kerusakan infrastruktur yang ada. Kata kunci: penggunaan lahan; zona bahaya tinggi; zona evakuasi; tsunami; kawasan pariwisata pesisir